Deep sequencing-derived Metagenome Assembled Genomes from the gut microbiome of liver transplant patients - Goutam Banerjee; Suraya Rahman Papri; Hai Huang; Sanjaya Kumar Satapathy; Pratik Banerjee (Scientific Data)
Abstract Recurrence of metabolic dysfunction-associated steatotic liver disease (MASLD) after liver transplantation (LT) is a continuing concern. The role of gut microbiome dysbiosis in MASLD initiation and progression has been well established. However, there is a lack of comprehensive gut microbiome shotgun sequence data for patients experiencing MASLD recurrence after LT. In this data descriptor, we describe a dataset of deep metagenomic sequences of a well-defined LT recipient population. Community-based analysis revealed a high abundance of Akkermansia muciniphila, consistently observed in most patient samples with a low (0–2) MASLD Activity Score (NAS). We constructed 357 metagenome-assembled genomes (MAGs), including 220 high-quality MAGs (>90% completion). The abundance of different species of Bacteroides MAGs dominated in patient samples with NAS > 5 (“definite MASH”). In contrast, the MAGs of A. muciniphila, Akkermansia sp., and Blutia sp. dominated in samples from patients without MASH (NAS = 0–2). In addition, the phylogenetic analysis of A. muciniphila and Akkermansia sp. MAGs identified two new phylogroups of Akkermansia that are distinct from the previously reported three phylogroups.